A First-Principles Study of Transport Properties in Armchair Germanene Nanoribbon Field Effect Transistors Subject to Metallic Dopants. (27th September 2021) - Samipour, Azam; Dideban, Daryoosh
Abstract : Density functional theory (DFT) in combination with non-equilibrium Green's function (NEGF) formalism are utilized to reveal the transport properties of armchair Germanene nanoribbon field effect transistors (AGeNR-FETs) subject to metallic dopants. Due to the semiconducting nature of p-type and n-type in the AGeNRs in the presence of In and Ag/Au dopants, these atoms are used at the source/drain electrodes to make FETs and Tunneling-FETs (TFETs). The transport properties of these transistors subject to Ag, Au and In atoms are analyzed with the aid of I–VDS, I–VG characteristics and transmission spectrum. It is shown that a negative differential resistance (NDR) is observed for each structure which occurs at low bias voltages. In particular, the maximum NDR with Ip /Iv = 14.78 is observed for the AGeNR-FET. From the transfer characteristics at VDS = 0.7 V it is also observed that depending on the type of impurity and the transistor, the minimum current decreases or increases, Dirac point shifts, and on-state current decreases. In addition, the highest Ion /Ioff ratio in FET is related to Ag-AGeNR structure with the value of 49 while for TFET it is related to In-Ag-AGeNR structure with a value of 6.4.